Pelacakan Kasus Flu Burung pada Ayam dengan Reverse Transcriptase Polymerase Chain Reaction* (DETECTION OF AVIAN INFLUENZA IN CHICKENS BY REVERSE TRANSCRIPTASE POLYMERASE CHAIN REACTION) - Kencana, Gusti Ayu Yuniati; Mahardika, I Gusti Ngurah Kade; Suardana, Ida Bagus Kade; Astawa, I Nyoman Mantik; Dewi, Ni Made Krisna; Putra, Gusti Ngurah Narendra (Jurnal Veteriner; Vol 13 No 3 (2012), 2013)
Avian Influenza (AI) or Bird Flu is a fatal zoonotic disease caused by highly pathogenic avian influenza(HPAI) virus of H5N1 sub-type. The disease is still endemic in Indonesia. This study was conducted toinvestigate AI cases in chickens in Bali. Virus isolation was performed in 9 day-old embryonated chickeneggs, and then followed by serologic testing by haemaglutination (HA) and Haemaglutination Inhibition(HI) assay using standard microtiter procedure. All of the samples were further tested with reversetrancriptasepolymerase chain reaction (RT-PCR). All work has been done in the Biomedical and MolecularBiology Laboratory, Faculty of Veterinary Medicine, Udayana University, Denpasar, during the period2009-2011. A total of ten samples were examined A total of ten chicken samples consisting of 6 fieldsamples and 4 meat samples have been confirmed to be AIV H5N1. All field cases showed clinical signsand gross pathology that were typical to the infection of avian influenza. The result indicates that AI casesare still prevalent among chickens in Bali.
Keywords: avian influenza, AI-H5N1, chicken, HA/HI, RT-PCR, Bali.